2005
DOI: 10.1002/chem.200500239
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Supported Heterogeneous Titanium Catalysts for Enantioselective Carbonyl–Ene and Sulfoxidation Reactions

Abstract: A new strategy for the heterogenization of chiral titanium complexes was developed by the in situ assembly of bridged multitopic BINOL ligands with [Ti(OiPr)4] without using a support. The assembled heterogeneous catalysts (self-supported) showed excellent enantioselectivity in both the carbonyl-ene reaction of alpha-methylstyrene with ethyl glyoxylate (up to 98 % ee) and the oxidation of sulfides (up to >99 % ee). The catalytic performance of these heterogeneous catalytic systems was comparable or even superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 94 publications
3
45
0
1
Order By: Relevance
“…Ti-binol has been supported on polystyrene [20], on an ionic liquid film deposited on a modified SBA-15 silica [21], or self-supported by using a polytopic binol ligand [22]. Very high enantioselectivities were obtained in the sulfoxidation with TBHP or CHP, combining the direct enantioselective sulfoxidation with a partial kinetic resolution by over-oxidation.…”
Section: Introductionmentioning
confidence: 97%
“…Ti-binol has been supported on polystyrene [20], on an ionic liquid film deposited on a modified SBA-15 silica [21], or self-supported by using a polytopic binol ligand [22]. Very high enantioselectivities were obtained in the sulfoxidation with TBHP or CHP, combining the direct enantioselective sulfoxidation with a partial kinetic resolution by over-oxidation.…”
Section: Introductionmentioning
confidence: 97%
“…[4,5] Therefore, asymmetric oxidation of prochiral sulfides is an attractive subject in organic synthesis. In the past two decades, asymmetric oxidation of sulfides has been extensively investigated, either promoted by Ti(O-i-Pr) 4 -chiral tartrates [6,7] and chiral organic compounds such as chiral oxaziridines, [8,9] or catalyzed by transition metal complexes of various chiral ligands, such as ironporphyrins, [10,11] manganese-salens, [12,13] titanium-BINOL, [14,15] titanium-C2-symmetric diols, [16,17] zirconium-trialkanol amines, [18] and vanadium- [19 -21] and iron- [22] tridentate Schiff base catalyst systems. Among these catalyst systems for asymmetric sulfoxidation, Bolm's catalysts, that is, VO(acac) 2 -and Fe(acac) 3 -Schiff base systems, have received considerable attention in recent years because of three attractive advantages: (1) the simplicity, convenient preparation, and easy modification of chiral Schiff base ligands; (2) the utilization of cheap and environmentally benign terminal oxidant (H 2 O 2 ); and (3) the facile reaction conditions and easy workup.…”
Section: Introductionmentioning
confidence: 99%
“…Bruce et al have reported the Polystyrene-bound cyclo-BINOLs for the Ti-catalyzed asymmetric oxidation of sulfides to sulfoxides with 78% ee and reusability up to three cycles [140]. Wang et al has utilized the self-supported strategy for the heterogenization of Ti-Binol complex which was highly stable and could be readily recycled and reused for over 1 month (at least eight cycles) without significant loss of activity and enantioselectivity (up to [99.9% ee) [141]. Fraile et al have immobilized Ti-diethyltartarate complex onto silica (Scheme 9) and got very good yield of sulfoxide with small (13%) asymmetric induction [142].…”
Section: Asymmetric Oxidation Of Sulfidesmentioning
confidence: 98%